Campus sustainability: Explaining students’ recycling behaviour using the TPB-moral norm framework - Che Nur Anis Atikah, Che Abdullah; Azim Azuan, Osman; Herb, Josephine (Universiti Malaysia Pahang, 2024)
The campus sustainability initiatives, including recycling, has become increasingly important for higher education institutions that aspire to be recognized in UI GreenMetric World University Rankings such as Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA). Hence, this study aims to enhance theoretical understanding of in-campus recycling practice and provide practical insights for effective communication and intervention strategies. The Theory of Planned Behavior was adopted to examine factors influencing UMPSA students’ engagement in recycling activities. A set of survey questionnaire form was utilized to collect quantitative data from a diverse sample of diploma, undergraduate, and postgraduate students at UMPSA. From the survey, 320 eligible respondents were successfully acquired and further analysed using IBM SPSS and SmartPLS 4. Ethical considerations (moral norms) and ease of recycling activities (perceived behavioural control) played a crucial role in determining UMPSA students’ intention to engage in recycling practices. The insights gained can guide interventions and educational programs to promote sustainable practices on campus. Future research could explore contextual nuances, like cultural or institutional factors at UMPSA, affecting recycling behaviour. Investigating intervention strategies to enhance moral norms, perceived behavioural control, and recycling intentions would further enrich sustainability initiatives at the university. The study sets the foundation for future research aiming to advance understanding and promote sustainable practices among university students.